2011
DOI: 10.1111/j.1443-1661.2010.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Prognosis After Endoscopic Resection for Submucosal Colorectal Carcinoma: Summary of a Multicenter Questionnaire Survey Conducted by the Colorectal Endoscopic Resection Standardization Implementation Working Group in Japanese Society for Cancer O

Abstract: We carried out a retrospective questionnaire survey of 792 submucosal colorectal carcinoma (CRC) cases from 15 institutions affiliated with the Colorectal Endoscopic Resection Standardization Implementation Working Group in Japanese Society for Cancer of the Colon and Rectum. In these cases, endoscopic resection (ER) and surveillance was carried out without additional surgical resection. Local recurrence or metastasis was observed in 18 cases. Local submucosal recurrence was observed in 11 cases, and metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 4 publications
2
35
1
Order By: Relevance
“…In a previous JSCCR research project, we reported mid‐term outcomes of endoscopically treated submucosal invasive colorectal carcinomas that were followed up without additional surgery, and the validity of the JSCCR guideline criteria under which endoscopic resection is considered to be curative 24 . The study confirmed that submucosal invasion < 1000 µm, well‐/moderately‐differentiated adenocarcinoma, and absence of vascular invasion are reliable criteria 24 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a previous JSCCR research project, we reported mid‐term outcomes of endoscopically treated submucosal invasive colorectal carcinomas that were followed up without additional surgery, and the validity of the JSCCR guideline criteria under which endoscopic resection is considered to be curative 24 . The study confirmed that submucosal invasion < 1000 µm, well‐/moderately‐differentiated adenocarcinoma, and absence of vascular invasion are reliable criteria 24 .…”
Section: Discussionmentioning
confidence: 66%
“…In a previous JSCCR research project, we reported mid‐term outcomes of endoscopically treated submucosal invasive colorectal carcinomas that were followed up without additional surgery, and the validity of the JSCCR guideline criteria under which endoscopic resection is considered to be curative 24 . The study confirmed that submucosal invasion < 1000 µm, well‐/moderately‐differentiated adenocarcinoma, and absence of vascular invasion are reliable criteria 24 . We have also previously reported that if differentiation of the submucosal invasive front is considered, complete cure by endoscopic treatment is possible for colorectal carcinomas invading the submucosa to a depth of 1500 µm but showing no vascular invasion 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the local and/or metastatic recurrence rate after endoscopic resection of T1 CRC was reported to be very low (0-2.3%) in the absence of risk factors for LN metastasis other than submucosal invasion depth [16,18,19,27]. Subsequent surgery is therefore not likely to be absolutely essential in all of these T1 CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, project research is currently in progress into other histopathological factors. Multi-center joint research projects have produced reports providing results from consideration of the appropriateness of these criteria [132][133][134]. None of the guidelines in other countries includes depth of invasion or budding as criteria for additional treatment.…”
Section: Clinical Questionsmentioning
confidence: 99%